2014
DOI: 10.1371/journal.pone.0090863
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Lipoic Acid Reduces LDL-Particle Number and PCSK9 Concentrations in High-Fat Fed Obese Zucker Rats

Abstract: We characterized the hypolipidemic effects of alpha-lipoic acid (LA, R-form) and examined the associated molecular mechanisms in a high fat fed Zucker rat model. Rats (n = 8) were assigned to a high fat (HF) diet or the HF diet with 0.25% LA (HF-LA) for 30 days and pair fed to remove confounding effects associated with the anorectic properties of LA. Compared with the HF controls, the HF-LA group was protected against diet-induced obesity (102.5±3.1 vs. 121.5±3.6,% change BW) and hypercholesterolemia with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 67 publications
(71 reference statements)
3
33
0
2
Order By: Relevance
“…Several animal (14,16) and human (17) studies have supported these finding even though none of them have reviewed the effect of ALA supplementation on lipid profile in patients with stroke. Consistent with the present study Carrier et al (14) examined the effects of ALA and its mechanism on lipid profile in high fat fed Zucker rats. In this study, rats were divided to 2 groups (a high fat diet or high fat diet with ALA for 30 days and pair fed to remove confounding effects of anti-appetite properties of ALA).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several animal (14,16) and human (17) studies have supported these finding even though none of them have reviewed the effect of ALA supplementation on lipid profile in patients with stroke. Consistent with the present study Carrier et al (14) examined the effects of ALA and its mechanism on lipid profile in high fat fed Zucker rats. In this study, rats were divided to 2 groups (a high fat diet or high fat diet with ALA for 30 days and pair fed to remove confounding effects of anti-appetite properties of ALA).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ALA protects the liver against TG accumulation via multiple mechanisms including: suppression of lipogenesis (down-regulation of hepatic acetyl-CoA carboxylase and fatty acid synthase expression); increase fat oxidation in liver (enhance carnitine palmitoyltransferase Ia expression); and increase export of VLDL (enhance hepatic diacylglycerol acyltransferase and microsomal triglyceride transfer protein expression and elevate number of plasma VLDL particles) (14,26,27). It is also reported that ALA enhances fatty acid uptake and oxidation in muscle tissue and is protective against increasing serum cholesterol and accumulating fat in liver under conditions of strong genetic and dietary predisposition toward obesity and dyslipidemia, without change in energy intake (4,14). In addition, it has been confirmed that ALA not only plays an important role in preventing fat accumulation (28,29) it even significantly reduces fat accumulation and appetite by regulating activities of central and peripheral adenosine monophosphate activated protein kinase (9,12,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total body pool of αLA from synthesis and ingestion of dietary sources including muscle, heart, kidney, and liver is low; therefore, the purported health effects of αLA are only observed following dietary supplementation, which have been investigated in the broad range of 600–1800 mg/d [11]. Data from our laboratory has previously shown that reductions in LDL-cholesterol and LDL-particle number following αLA supplementation were associated with lower circulating concentrations of proprotein convertase subtilisin/kexin type 9 (PCSK9), a primary regulator of LDLr protein turnover [12]. αLA supplementation was recently shown to reduce atherosclerotic plaque formation by reducing aortic lipid and inflammatory cell infiltration in Watanabe heritable hyperlipidemic rabbits in the absence of any change in plasma lipids [13].…”
Section: Introductionmentioning
confidence: 99%